Heart transplantation: comparing the impact of modified heart preservation with conventional methods - Xiaoke Shang; Changdong Zhang; Yixuan Wang; Mei Liu; Yucheng Zhong; Nianguo Dong (Scientific Reports)
Abstract The purpose of this study was to compare the impact of modified heart preservation techniques with conventional heart preservation techniques on heart transplant recipients. The goal was to determine if these modified preservation techniques could extend the preservation of the donor heart without increasing the risk of recipient mortality. A retrospective analysis was carried out on 763 cases of orthotopic heart transplantation performed at Wuhan Union Hospital and Nanjing First Hospital, from September 2008 to October 2022. Among these, 656 cases underwent modified heart preservation and were assigned to the study group, while 107 cases underwent conventional heart preservation and were designated as the control group. Detailed information from both groups was collected and compared, including demographic and donor characteristics, survival status, disease type, and recipient/donor characteristics. The study revealed that the modified heart preservation method did not increase the risk of mortality compared to the conventional method. However, it was found that patient factors such as diagnostic classification, recipient age, and donor age significantly influenced mortality risk and were strongly associated with patient survival. The preservation time of the donor heart was significantly longer in the study group compared to the control group, without affecting the survival of the transplant recipients. The findings of our study suggest that modified heart preservation techniques hold promise as a potential method for prolonging heart preservation time. Despite extending the preservation period, these modified techniques did not increase the mortality risk in heart transplant recipients. This could potentially allow for more flexibility in the long-distance transport and preservation of hearts, thereby broadening the scope of viable donors for heart transplantation.